2018
DOI: 10.1002/acr.23484
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Total Knee Replacement: Population Losses in Quality‐Adjusted Life‐Years Due to Differential Offer, Acceptance, and Complication Rates for African Americans

Abstract: African Americans lose 72,000 QALYs due to disparities in TKR offer and complication rates. Programs to decrease disparities in TKR use are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Higher prevalence of continuous opioid use among African Americans could be partly due to multi-level barriers prior to the final decision on the TJR surgery. These barriers include differential access to healthcare facilities, surgeon preferences, and patient preference, acceptance or expectations of the surgery 27,29 . Furthermore, the present study showed associations between geographic regions and continuous opioid use prior to TJR, where patients from the Midwest and South were more likely to be continuous opioid users compared to patients from the Northeast.…”
Section: Discussionmentioning
confidence: 99%
“…Higher prevalence of continuous opioid use among African Americans could be partly due to multi-level barriers prior to the final decision on the TJR surgery. These barriers include differential access to healthcare facilities, surgeon preferences, and patient preference, acceptance or expectations of the surgery 27,29 . Furthermore, the present study showed associations between geographic regions and continuous opioid use prior to TJR, where patients from the Midwest and South were more likely to be continuous opioid users compared to patients from the Northeast.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in TJA use among minority patients has societal and economic implications. Kerman et al ( 14 ) used a Markov simulation model to predict the number of quality‐adjusted life‐years (QALYs) lost by Black patients because of lower TKA use. Assuming 40% lower use of TKA by Black patients compared with White patients, they estimated 72,000 QALYs lost by Black patients ( 14 ).…”
Section: Racial Disparities In Tja Usementioning
confidence: 99%
“…A recent study performed by Kermann and colleagues used a validated computer simulation model (Osteoarthritis Policy Model) of the natural history and treatment of knee OA to estimate QALY in Black and White patients with and without TKA. According to the data, Black patients gain fewer QALYs (per 100 patients) from TKA compared with White patients (see Figure 5) [69].…”
Section: Utilization Of Other Treatments Apart From Surgery and Treatment Recommendationsmentioning
confidence: 99%
“…Key insight [66,69]. A study by Goodman and colleagues investigated whether race and socioeconomic factors at the individual level were associated with patient-reported pain and function, Key insight [66,69].…”
Section: The Influence Of Poverty On Racial Disparity In Treatment Outcomesmentioning
confidence: 99%
See 1 more Smart Citation